Influential Behavioral Factors on Retirement Planning Behavior: The Case of Malaysia - Fatemeh, Kimiyagahlam; Meysam, Safari; Shaheen, Mansori (Springer Publishing, 2019)
The main objective of this research is to identify the behavioral factors which have an effect on retirement planning behavior. The study applies the theory of planned behavior and time perspective theory as a basis for the analysis of data by the structural equation modeling technique from a sample of 900 adults in Kelang Valley, Malaysia. The results of structural equation modeling show that financial literacy, propensity to plan, and future orientation are directly associated with retirement planning behavior. The saving attitude is also found to partially mediate these relationships. However, family education and materialism are not associated with retirement planning. Implications for researchers and practitioners are presented.